Effect of Landfill Leachates on Some Water Quality Indicators of Selected Surface Water and Groundwater at Ilokun, Ado-Ekiti, Nigeria - Omofunmi, Olorunwa; Satimehin, Adesola; Oloye, Abraham; Umego, Okwunna (Makara Journal of Technology, 2020)
This study was conducted to examine the impact of dumpsites on the quality of groundwater and surface water. The water samples and leachates were collected from dumpsites in respective zones. The physicochemical properties of the samples were examined and determined in accordance with the standards of the American Public Health Association. Results indicated that the groundwater and surface water that are close to the dumpsites have an electrical conductivity of 385 and 245 Sd/cm, total dissolved solids of 168 and 128 mg/L, a turbidity of 4.6 and 22 NTU, a total alkalinity of 103 and 50 mg/L, a total hardness of 120 and 80 mg/L, Ca concentration of 44 and 14 mg/L, Mg concentration of 0.2 and 15 mg/L, SO4 concentration of 4 and 42 mg/L, Cl concentration of 38 and 16 mg/L, and NO3 concentration of 6 and 8 mg/L, respectively. Moreover, the water near the dumpsites had higher elevated physicochemical properties compared with those far from the dumpsites; in addition, they were significantly different (p ≥ 0.05). Hence, the closer the groundwater and surface water to the dumpsite, the greater the negative impact on the physicochemical properties of water. The pH concentration in leachate serves as an indicator for the age and mineralization status of dumpsites, and it influences the other chemical properties of the leachate. Furthermore, the pH concentration in leachate is inversely proportional to the concentration of Ca, Mg, and SO4 in the study area.